RESOURCE USE EFFICIENCY OF POULTRY LAYERS PRODUCTION IN ROGO LOCAL GOVERNMENT AREA KANO STATE, NIGERIA - Zarewa Muhammad NALAMI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was carried out to determine the resource use efficiency of poultry-layers production in Rogo Local Government Area of Kano State. A sample of 150 farmers was selected by simple random sampling technique. The data was analyzed using descriptive statistics, frequency, percentage, multiple regression and marginal analysis. The result reveals that, the cost incurred on purchasing chicks has significant at 1%; medication has significant at 5% and labour at 5%. The positive nature of the relationship of the chicks, medication and labour means increase at one unit of chick; medication and labour would cause the quantity of output to increase by certain percentage. The negative relationship of electricity to the returns implies that decrease in one unit cost of the input will cause the return to decrease by certain percentage. The result indicates that all the variables inputs in the production were inefficiently utilized because none of the ratio equals to one. The farmers under-utilized the chicks, electricity and medication. The labour ratio is less than one showing that the farmers over-utilized labour. The result indicates the need for making input affordable and accessible to farmers so as to improve efficiency. It also implies that the farmers might be earning higher returns if more of the various resources were efficiently utilized. It was also recommended that poultry layers farmers should implement better management practices to minimize the incident of their resource used inefficiently to improve the profitability and resource use efficiency of poultry production.